Stewart Julian Wallace (1954–2022): Contributor to Global Telecommunications and Life - Vinnal, Enn (Journal of Telecommunications and the Digital Economy, 2023)
Stewart Wallace made many contributions in his life, most notably to the development of the APT700 frequency band, the Asia Pacific Telecommunity 700 MHz spectrum, now used on mobile phones in many parts of the world. He was also an admired bagpiper, invited to play at Royal Edinburgh Military Tattoos, ANZAC commemorations and as a solo piper. Through the diversity of his upbringing, education, varied life experiences, and openness to new challenges, together with passion for each of these while also being a good listener and communicator, Stewart Wallace achieved an enviable balance of humanity and global success, doing what he loved best.